Inhibition Of Leaf Extract of Rubber Plant Against Enterobacteriaceae Isolated from Drinking Water Refill - Fitri Kusuma, Sri Agung - (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Antibacterial resistance in pathogenic bacteria and their contamination in water are contributing to the spreading of infectious diseases. As a result, isolation and antimicrobial susceptibility testing for drinking water samples are becoming increasingly important in addressing the human health hazards associated with ingesting contaminated water. Therefore, this study was aimed to identify enterobacteria strains in drinking water refill obtained from 20 refill water stations in Jatinangor, West Java, Indonesia and investigated the potential antibacterial activity of rubber plant (Ficus elastica Roxb. ex Hornem) leaf extracts on identified strains of the isolated enterobacteria. Bacterial isolation was accomplished using membrane filtration method and the bacterial identification was performed by observing the cell and colonies morphologies, biochemical testing approach and concluded using the computer program Global Infectious Diseases and Epidemiology Network (GIDEON). The antimicrobial susceptibility test was carried out using the Kirby-Bauer diffusion technique. From 20 water samples, we isolated 30 single colonies which composed of four strains of identified Enterobacteriaceae, as follows: Citrobacter freundii (nine samples), Salmonella typhi (six samples), Serratia marescens (six samples) and Escherichia coli (nine samples) with percentage: 30%, 20%, 20% and 30%, respectively. The extract can inhibit all Enterobacteria isolates, however, among those strains, E. coli was the most susceptible Enterobacteria to be inhibited by F. elastica leaf extract. The current study suggests that this plant potentially to be used as a novel antibacterial agent against Enterobacteria strains as the major gastrointestinal tract pathogenic microbes.